2011
DOI: 10.11606/issn.2176-7262.v44i3p234-240
|View full text |Cite
|
Sign up to set email alerts
|

Papel dos ácidos graxos ômega 3 na resolução dos processos inflamatórios

Abstract: Artigo recebido em 09/12/2010 Aprovado para publicação em 13/09/2011 P P P P Pa a a a apel dos ácidos g pel dos ácidos g pel dos ácidos g pel dos ácidos g pel dos ácidos gr r r r rax ax ax ax axos ôme os ôme os ôme os ôme os ômeg g g g ga 3 na a 3 na a 3 na a 3 na a 3 na r r r r resolução dos pr esolução dos pr esolução dos pr esolução dos pr esolução dos processos inf ocessos inf ocessos inf ocessos inf ocessos inflama lama lama lama lamatórios tórios tórios tórios tórios RESUMOA inflamação é uma resposta de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
1
0
7
Order By: Relevance
“…Several studies have reported the importance of lipids present in fish because they are a source of long chain polyunsaturated fatty acids. The fatty acids of the omega-3 series, such as eicosapentaenoic (EPA) and docosahexaenoic (DHA), have received greater attention because they are related to the minimization of inflammatory processes (Barbalho et al, 2011), reduction of risk of disease development (Santos & Bortolozo, 2008), asthma, hypertension, lupus, skin and eye diseases, depression (Guiné & Henriques, 2011) and Alzheimer's disease (Domínguez, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the importance of lipids present in fish because they are a source of long chain polyunsaturated fatty acids. The fatty acids of the omega-3 series, such as eicosapentaenoic (EPA) and docosahexaenoic (DHA), have received greater attention because they are related to the minimization of inflammatory processes (Barbalho et al, 2011), reduction of risk of disease development (Santos & Bortolozo, 2008), asthma, hypertension, lupus, skin and eye diseases, depression (Guiné & Henriques, 2011) and Alzheimer's disease (Domínguez, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Serhan, 2008;Levy, 2010;Devchand, et al 2005;Arita, 2005;Bueno Jr, 2009). Entre os principais mecanismos que podem explicar os efeitos benéficos dos Ômega 3 está a competição com o ômega 6 pelo substrato que previne a conversão do ácido araquidônico em eicosanoides pró-inflamatórios como as prostaglandinas, leucotrienos e lipoxinas (Barbalho et al, 2011), exercendo um efeito inibidor da proliferação de células cancerígenas.…”
Section: áCidos Graxosunclassified
“…Adicionalmente, os ácidos graxos ômega-3 podem ser agentes protetores de doenças inflamatórias como, por exemplo, doença vascular aterosclerótica, artrite, alergias, entre outras (Barbalho, Bechara, Quesada & Goulart, 2011). Segundo a Food and Agriculture Research, Society and Development, v. 9, n. 12, e42191211158, 2020 (CC BY 4. Organization e World Health Organization os probióticos podem ser definidos como "microrganismos vivos que, quando administrados em quantidade adequada, conferem benefício para a saúde do consumidor".…”
Section: Terapia Nutricionalunclassified